Factors Determining The Success Of Providing Social Assistance To Fishermen In Coastal Areas From A Public Service Perspective - Erdawat, Mega; Asdar, H A; Zulkifli, Zulkifli; Asrijal, Andi (Jurnal Ekonomi, 2024)
This study aims to analyze the economic, social, and institutional factors that influence the success of social assistance programs to fishermen in coastal areas and identify challenges in program implementation from a public service perspective. The results show that economic factors such as livelihood diversification, profitability of fisheries, fisheries subsidies, availability of human resources, and profit transfer are crucial for program sustainability. Social aspects such as community participation, cooperation in fisheries, and involvement of indigenous people also play an important role. Strong institutional support is necessary, but challenges such as aid dependency, poor infrastructure, and bureaucratic barriers exist. This research provides a solid foundation for understanding the factors that influence the success of social assistance programs and provides policy recommendations that can be implemented to improve the welfare of fishers in coastal areas.